Inactivation of multidrug-resistant bacteria using cold atmospheric-pressure plasma technology - Wang, Xingxing; Chen, Mengzhen; Lu, Ye; Yu, Peihao; Zhang, Chen; Huang, Chao; Yang, Zhibiao; Chen, Yan; Zhou, Jian-cang (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to investigate the impact of cold atmospheric-pressure plasma (CAP) on multidrug-resistant (MDR) bacteria on various surfaces under nosocomial circumstances and the underlying mechanism.MethodFour common MDR bacteria (carbapenem-resistant Acinetobacter baumannii, carbapenem-resistant Pseudomonas aeruginosa, methicillin-resistant Staphylococcus aureus, and carbapenem-resistant Klebsiella pneumoniae) were inoculated on nosocomial surfaces, which were subsequently exposed to CAP. Then the bacteria from surfaces were recovered and diluted. The killing curve was analyzed to evaluate the sterilization effects of CAP. Electron microscopy was used to evaluate the changes in cell morphology.ResultIn the CAP-producing device, most of the MDR bacteria were nearly inactivated after 2 h of CAP treatment. Under the simulated ward, CAP exerted an inactivating effect on MDR bacteria. Scanning electron microscopy revealed that the surface of MDR bacteria became blurred, the bodies ruptured and adhered to each other after CAP treatment. The cell walls were thinner as revealed by transmission electron microscopy.ConclusionCAP could inactivate the most common MDR bacteria on nosocomial surfaces in simulation ward settings by destroying the structure of pathogens. Our data provided insights into the sterilization of MDR bacteria using CAP and suggested a novel in-hospital disinfection alternative.